Soft Lithography and Minimally Human Invasive Technique for Rapid Screening of Oral Biofilm Formation on New Microfabricated Dental Material Surfaces. (2023)
Microfabrication offers opportunities to study surface concepts focused to reduce bacterial adhesion on implants using human minimally invasive rapid screening (hMIRS). Wide information is available about cell/biomaterial interactions using eukaryotic and prokaryotic cells on surfaces of dental materials with different topographies, but studies using human being are still limited.